Antioxidant Bioaccessibility of Cooked Gluten-Free Pasta Enriched with Tomato Pomace or Linseed Meal - Lorenzo Estivi; Gabriella Pasini; Amel Betrouche; Vanja Traviĉić; Elena Becciu; Andrea Brandolini; Alyssa Hidalgo (Foods)
Gluten-free products lack bioactive compounds, while vegetable wastes from food manufacturing are still rich in nutrients. This study compared the antioxidants of gluten-free pastas enriched with vegetable by-products: the control formulation (66.7% rice and 33.3% fava bean flours) was enriched with 10% or 15% of tomato waste (TO) or defatted linseed cake (LI). Carotenoids, tocols, phenolics, and antioxidant capacity (ABTS and FRAP) were determined in the cooked pasta as well as in the soluble and insoluble fractions after in vitro gastro-intestinal digestion. The cooked enriched pastas showed higher levels of carotenoids (1.36–1.53 vs. 1.02 mg/kg DM), except for the LI-added samples, tocols (8.83–21.70 vs. 7.01 mg/kg DM), free polyphenols (218.1–258.6 vs. 200.9 mg/kg DM), bound polyphenols (132.7–177.6 vs. 101.9 mg/kg DM), and antioxidant capacity. Cooking augmented the carotenoids and free polyphenols in the enriched pastas, tocols in LI pastas and bound flavonoids in TO pastas. After digestion, the recoveries for soluble and insoluble fractions were 53% and 35% for carotenoids, 52% and 43% for tocols, 109% for free phenolic acids, 97% for free flavonoids, 93% for bound phenolic acids, and 100% for bound flavonoids. Bioaccessibility was the highest for free phenolic compounds, whereas carotenoids and tocols were partially available.